Germany's 9-Euro ticket: Impact of a cheap public transport ticket on mobility patterns and infrastructure quality - Mario Liebensteiner; Jakob Losert; Sarah Necker; Florian Neumeier; Jörg Paetzold; Sebastian Wichert (EconPol Forum, 2025)
The 9-Euro Ticket increased public transport use but hardly shifted away from car travel. Train use surged for leisure activities; car use dropped least among commuters. The 9-Euro Ticket led to overcrowding, delaying both regional and non-covered long-distance trains. A rough calculation indicates that the fuel discount minimally impacted our estimates. High costs, low car-to-train shift, and train delays call for other decarbonization strategies.
Keywords: 330